Pengaruh tarif pajak, pemahaman perpajakan, dan sanksi perpajakan terhadap kepatuhan wajib pajak UMKM Kota Pati - Arta, Luky Dani; Alfasadun, Alfasadun (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Micro, Small and Medium Enterprises (MSME) are one of the sectors that have the potential to contribute to state tax revenues. MSME taxpayer compliance is still very low, especially MSME taxpayer compliance in Pati City has not yet reached 50%. The purpose of this study was to examine the effect of tax rates, understanding of taxation and tax sanction on MSME taxpayer compliance. The theory used in this research is the theory of planned behavior and attribution theory. As much 102 MSME taxpayers were randomly selected as respondents using the slovin formula. The method of determining the sample in this study was accidental sampling and the technical analysis of the data in this study used multiple linear regression analysis which is processed in the SPSS version 25 program. The result showed that tax rates, understanding of taxation and tax sanction have a positive effect on MSME taxpayer compliance either simultaneously or partially.